First preliminary results for the absolute calibration of the Chinese HY-2 altimetric mission using the CRS1 calibration facilities in West Crete, Greece. Issue 1 (1st January 2016) - Mertikas, Stelios P.; Zhou, Xinghua; Qiao, Fangli; Daskalakis, Antonis; Lin, Mingsen; Peng, Hailong; Tziavos, Ilias N.; Vergos, George; Tripolitsiotis, Achilleas; Frantzis, Xenophon
Abstract: In this work, absolute calibration of the Chinese HY-2 satellite altimetry mission is carried out, employing Pass No. 280 and the calibration facility, CRS1, located in the Southwest end of the island of Crete, Greece. Satellite Pass No. 280 is descending and follows a ground track almost parallel to the west coast of Crete. It comes close to the coast, at a distance of about 9 km from the CRS1 calibration site, and finally goes away south of Crete. The HY-2 sensor geophysical data records (S-GDR) have been incorporated into the calibration procedures and processing has taken place for cycles No. 54–62, at 20 Hz data rate. Some peculiarities in the HY-2 satellite altimeter data, as delivered and depicted in the I-GDR and S-GDR data, have also been noticed. All calibration results have been determined using a regional, precise and detailed geoid, along with a good knowledge of local ocean circulation and site characteristics and a well-defined sea-surface calibration methodology. The first preliminary results for the HY-2 altimeter calibration have shown that the initial cycles, up to No. 51, display an erratic behavior. After those cycles, the altimeter range bias values seem to be stable and reach a value of B = −45.6 cm ± 4.4 cm, when applying the net instrument corrections as provided in the GDR. If the relativistic effects of the satellite clocks are properly applied for the net instrument corrections, then the altimeter range bias goes down to B = −27 cm ± 3 cm. Also, preliminary cross-over analysis with the SARAL/AliKa and Jason-2 satellites show a bias of B = −23 cm, and B = −28.5 cm, respectively. The performance of the HY-2 on-board radiometer has also been examined in terms of the wet troposphere corrections and shows a mean difference of −1 cm ± 0.1 cm with respect to in-situ GNSS-derived corrections. Finally, the ionosphere path corrections of the HY-2 satellite show a difference of +1 cm ± 1.1 cm, when compared against the GNSS-derived ionosphere values.